Coulomb-gauge calculation of the combined effect of correlation and QED for heliumlike highly charged ions - Holmberg, Johan; Salomonson, Sten; Lindgren, Ingvar (Physical review. A, Atomic, molecular, and optical physics, 2015)
We present numerical results for the energy shift due to the combination of Coulomb-correlation and quantum-electrodynamic effects in the ground state of heliumlike highly charged ions. The combined effect of two or more Coulomb interactions together with a single retarded photon, including radiative effects, is calculated for various atomic numbers in the range Z=14 to Z=50. One step in our computational scheme involves the evaluation of the Coulomb-screened self-energy at the two-photon level, and we present a detailed comparison between the Coulomb and Feynman gauges with regard to the various contributions to this effect.
Gesehen am 07.09.2020